2010
DOI: 10.1051/0004-6361/201015198
|View full text |Cite
|
Sign up to set email alerts
|

Cold fronts and multi-temperature structures in the core of Abell 2052

Abstract: Context. The physics of the coolest phases in the hot intra-cluster medium (ICM) of clusters of galaxies is yet to be fully unveiled. X-ray cavities blown by the central active galactic nucleus (AGN) contain enough energy to heat the surrounding gas and stop cooling, but locally blobs or filaments of gas appear to be able to cool to low temperatures of 10 4 K. In X-rays, however, gas with temperatures lower than 0.5 keV is not observed. Aims. We aim to find spatial and multi-temperature structures in the hot g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
(104 reference statements)
1
14
1
Order By: Relevance
“…Deep observations of several cooling flow clusters have shown that the picture of a complete cut off in the X-ray temperature distribution is incorrect. There are many cases now showing clusters with cool X-ray emitting gas embedded in a hotter medium, associated with emission line filaments, including Centaurus , Abell 2204, (Sanders, Fabian & Taylor 2009b), 2A 0335+096 (Sanders, Fabian & Taylor 2009a), Abell 2052(de Plaa et al 2010), M87 , Sérsic 159 (Werner et al 2011), Abell 262 and Abell 3581 (Sanders et al 2010) and in several elliptical galaxies (Werner et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Deep observations of several cooling flow clusters have shown that the picture of a complete cut off in the X-ray temperature distribution is incorrect. There are many cases now showing clusters with cool X-ray emitting gas embedded in a hotter medium, associated with emission line filaments, including Centaurus , Abell 2204, (Sanders, Fabian & Taylor 2009b), 2A 0335+096 (Sanders, Fabian & Taylor 2009a), Abell 2052(de Plaa et al 2010), M87 , Sérsic 159 (Werner et al 2011), Abell 262 and Abell 3581 (Sanders et al 2010) and in several elliptical galaxies (Werner et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively dense uplifted X-ray-emitting gas, which is removed from the direct influence of the AGN jets, will cool in the absence of heating and eventually form stars. Multiphase cooling X-ray gas, displaced from the centre of the cD galaxy and spatially coincident with Hα emission, has also been seen in the Ophiuchus Cluster, in Abell 2052 and in MACS J1931.8−2634 (Edwards et al 2009;de Plaa et al 2010;Million et al 2010b;Ehlert et al 2011).…”
Section: Cooling Of the Displaced Gas And Star Formationmentioning
confidence: 97%
“…However, relatively little attention has been paid to the metallicity properties of cold fronts (see, e.g., Simionescu et al 2010;de Plaa et al 2010), especially in the sloshing scenario of cool core clusters. These clusters have prominent metallicity peaks in their centers (e.g.…”
Section: Introductionmentioning
confidence: 99%